Development and validation of career decision making proficiency scale - Khawaja, Sarwar; Javed, Ruqaiya; Qureshi, Fayyaz Hussain (Journal of Asian Scientific Research, 2024)
The purpose of the present research was to develop and examine the psychometric properties of the Career Decision Making Proficiency Scale (CDMPS). The new tool amalgamates various conceptual domains of career exploration process and validates its usage for students and young adults (N=565). The researcher used a survey research design that involved the theoretical evaluation by experts, mandating two subscale divisions for the original 40 items. A deductive approach was considered for the scale development. The content validity assessment by means of CVR- Lawshe’s Test, Fleiss’ Kappa statistics, and the CVI-proportion agreement method retained 34 items. R Studio software was used for dimension reduction techniques and inter-factor bi-variate correlations. The results of the item analysis confirmed 30 items clustered into five dormant constructs. The reliability coefficients of the two sub-scales were found to be high (α= 0.80 and 0.87). Furthermore, the exploratory factor analysis explained 52.45 percent and 50.99 percent of total variance, confirming the factorial internal structural validity of the two sub-scales, respectively. The scale can be administered by career and school counsellors to guide students with their career decisions, to assess career decision difficulties faced by weak students and potential dropouts or repeaters, and to assess students’ confidence, motivation, and abilities in handling problematic situations at the time of deciding a career path.